2019
DOI: 10.1542/peds.2018-2469
|View full text |Cite
|
Sign up to set email alerts
|

Giant Congenital Melanocytic Nevus Treated With Trametinib

Abstract: Giant congenital nevi are melanocytic proliferations of the skin that may be complicated by melanoma, neurocutaneous melanocytosis, pain, pruritus, and disfigurement. Current treatment options include surgical resection and medical management of associated symptoms. There is limited efficacy in these modalities. No effective pharmacologic treatments are available for the treatment of these lesions. We present the case of a 7-year-old girl with a giant congenital melanocytic nevus that had an AKAP9-BRAF fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 14 publications
(19 reference statements)
2
44
0
2
Order By: Relevance
“…Another study found a gain of function mutation in the NRAS gene associated with GCMN, ultimately leading to an abnormal proliferation of melanoblasts [9]. Some literature reports BRAFactivating mutations (single-nucleotide variants and fusions) activate the MAPK pathway [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found a gain of function mutation in the NRAS gene associated with GCMN, ultimately leading to an abnormal proliferation of melanoblasts [9]. Some literature reports BRAFactivating mutations (single-nucleotide variants and fusions) activate the MAPK pathway [5].…”
Section: Discussionmentioning
confidence: 99%
“…CMN are usually categorized depending on the adult size of maximum diameter of the lesion into small, medium, large or giant nevi. Small CMNs are usually <1.5cm, medium 1.5-19.9cm, large 20-40cm and giant >40cm in maximal diameter [4,5]. This classification is also accepted and stated by the University of New York [6].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies provide information for a comprehensive understanding of CMN, and molecular targeted therapies also provide new management strategies, especially for large to giant CMN, since traditional treatment relies heavily on surgical excision procedures. In 2019, Mir A et al [21] reported the first targeted therapy in a BRAF-mutated giant CMN with trametinib, a MEK inhibitor. Later, Rouille et al [22] reported that the proliferative potential of CMN could be limited by local administration of MEK and Akt inhibitors in a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies add information for the diagnosis and evaluation of malignant potential, and the subsequent molecular targeted drugs also provide new management strategies for giant CMNs since traditional treatment relies heavily upon iterative surgical procedures, such as excision and curettage. Mir A et al [28] reported the first BRAF-mutated giant CMN treated with trametinib, an MEK inhibitor. The color and extent of the nevus lesion improved, and the patient's intractable pain and pruritus rapidly resolved.…”
Section: Discussionmentioning
confidence: 99%